"I Really Belong Here": Civic Capacity‐Building among Returning Citizens. Issue 3 (21st July 2020) - Cossyleon, Jennifer E.; Flores, Edward O.
Abstract : This article focuses on unlikely movement actors whose civic engagement has been understudied: people with criminal records ("returning citizens"). We present findings from 18 months of ethnographic research with members (leaders) of Fighting to Overcome Records and Create Equality (FORCE), a civic group led by returning citizens. FORCE leaders received institutional support from Community Renewal Society (CRS), a larger faith and community‐based organization, to lead a rights reform movement in Chicago. Findings suggest that FORCE leaders constructed notions of kinship, recognition, and power through civic capacity‐building efforts—and that social belonging was core to such capacity‐building efforts. While bonding social belonging occurred as FORCE leaders formed kinship with people facing similar social and economic marginality, bridging social belonging emerged as leaders felt recognized by CRS staff organizers, affiliates, and elected officials. Bonding and bridging social belonging enabled FORCE leaders, who faced constant social exclusion in society, to experience much needed kinship, recognition, and power. Future studies should continue to uncover how local capacity‐building processes have life‐changing relational effects on movement participants from socially and economically marginalized groups.